Cellular and Molecular Networking Within the Ecosystem of Cancer Cell Communication via Tunneling Nanotubes - Lou, Emil; Zhai, Edward; Sarkari, Akshat; Desir, Snider; Wong, Phillip; Iizuka, Yoshie; Yang, Jianbo; Subramanian, Subbaya; McCarthy, James; Bazzaro, Martina; Steer, Clifford J. (Frontiers in Cell and Developmental Biology, 2018)
Intercellular communication is vital to the ecosystem of cancer cell organization and invasion. Identification of key cellular cargo and their varied modes of transport are important considerations in understanding the basic mechanisms of cancer cell growth. Gap junctions, exosomes, and apoptotic bodies play key roles as physical modalities in mediating intercellular transport. Tunneling nanotubes (TNTs) — narrow actin-based cytoplasmic extensions — are unique structures that facilitate direct, long distance cell-to-cell transport of cargo, including microRNAs, mitochondria, and a variety of other sub-cellular components. The transport of cargo via TNTs occurs between malignant and stromal cells and can lead to changes in gene regulation that propagate the cancer phenotype. More notably, the transfer of these varied molecules almost invariably plays a critical role in the communication between cancer cells themselves in an effort to resist death by chemotherapy and promote the growth and metastases of the primary oncogenic cell. The more traditional definition of “Systems Biology” is the computational and mathematical modeling of complex biological systems. The concept, however, is now used more widely in biology in a variety of contexts, including interdisciplinary fields of study that focus on complex interactions within biological systems and how these interactions give rise to the function and behavior of such systems. Indeed, it is imperative to understand and reconstruct components in their native context rather than examining them separately. The long-term objective of evaluating cancer ecosystems in their proper context is to better diagnose, classify, and more accurately predict the outcome of treatment for cancer. Communication is key to the advancement and evolution of the tumor ecosystem. This interplay results in cancer progression. As key mediators of intercellular communication within the tumor ecosystem, TNTs are the central topic of this article.